A statistical quality control study on Fil-Pacific Apparel, Incorporated - Espejo, Emiluz M.; Pangan, Mario M. Jr.; Tablante, Rinna C. (Diliman, Quezon City College of Engineering, 1997)
The company under study is FIL-PACIFIC APPAREL CORPORATION, a garments manufacturer for export. They are a company division under the Manufacturing Director?s Office. They manufacture jeans, jackets, slacks and other clothing. The company has 4 assembly lines and one finish line, with each line producing the same or different style of garment. Inspectors are located at the end of each line. Data gathering was done through numerous plant visits and interviews with the Production Manager, Engineering Manager, Inspectors and Quality Controllers, and the workers. Through proper sorting and analysis of relevant data, it was seen that during the months of July and August 1996, waistband defects have the highest occurrence. The team recommends a methods study on the improvement of the production of the waistband part and the establishment of proper training system for the newly-hired workers. The team also recommends a forms design improvement to emend the company?s record-keeping. A better forms design would also eliminate irrelevant information and only include the important ones.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Fil-Pacific Apparel Incorporated; Clothing trade; Quality control